A Comprehensive Phylogeny of Tettigoniidae (Orthoptera: Ensifera) Reveals Extensive Ecomorph Convergence and Widespread Taxonomic Incongruence. Issue 4 (14th August 2018) - Mugleston, Joseph D; Naegle, Michael; Song, Hojun; Whiting, Michael F
Abstract: Tettigoniidae (katydids) are a diverse group of insects that are well known for their leaf-like camouflage and acoustic signaling. We present the first comprehensive phylogenetic analysis of katydids based on five molecular markers (18S rDNA, 28S rDNA, cytochrome c oxidase II, wingless, and histone 3) for 235 katydid taxa representing the overall diversity of the group. We specifically investigate the monophyly of katydid subfamilies and tribes and elucidate the origins and subsequent dispersal of katydids that has led to their cosmopolitan distribution. Katydids diverged from their ensiferan ancestor in the late Jurassic (~155 MYA) and multiple transoceanic dispersals have resulted in katydids inhabiting nearly every terrestrial biome outside the arctic regions. We find that the subfamilies Zaprochilinae, Saginae, Pterochrozinae, Conocephalinae, Hexacentrinae, Hetrodinae, Austrosaginae, and Lipotactinae are monophyletic while Meconematinae, Listroscelidinae, Tettigoniinae, Pseudophyllinae, Phaneropterinae, Mecopodinae, and Bradyporinae are paraphyletic. This widespread paraphyly is largely due to the convergent evolution of ecomorphs across different continents. Consequently, many of the characters that delineate the subfamilies are convergent, and in many cases biogeography is a better predictor of relationships than taxonomy. We provide a summary of taxonomic changes to better bring katydid taxonomy in line with their phylogeny.